Strategi Komisi Pemilihan Umum Labuhan Batu dalam Meningkatkan Partisipasi Pemilih Dalam Pemilihan Kepala Daerah Labuhan Batu 2020 Melalui Media Sosial - Ayunda Putri Rambe; Iskandar Zulkarnain; Hatta Ridho (Universitas Medan Area, 2023)
The purpose of this study is to find out how the Labuhan Batu Regency KPU's strategy is in increasing voter participation in the Regional Head election. The method used in this study is a qualitative method with in-depth interviews. The subject of this research is the Commissioner of Socialization Division of Community Participation and HR. The data collection technique used in this study can be of two parts, namely primary data sources and secondary data sources, primary data, namely data from interviews, while secondary data is data obtained from documents related to this research and the analysis technique used is qualitative analysis. descriptive in nature. The results of the study show that the strategy carried out by the General Election Commission of Labuhan Batu Regency in increasing voter participation in the 2020 Regional Head election can be seen from the form of socialization, namely by using social media and electronic media. The inhibiting factor in voter participation occurs because there are still people who do not care or are indifferent to existing politics. Through the strategy of the General Election Commission for Labuhan Batu Regency, there was an increase in voter participation in the 2020 Regional Head Election of Labuhan Batu Regency, namely reaching 75% in 2020 compared to the previous participation in 2015 of 64.14%.